The response of nutrient cycle, microbial community abundance and metabolic function to nitrogen fertilizer in rhizosphere soil of Phellodendron chinense Schneid seedlings - Gu, Yuanzheng; Chen, Xianglin; Shen, Yan; Chen, Xiaoyong; He, Gongxiu; He, Xinxing; Wang, Guangjun; He, Hanjie; Lv, Zhencheng (Frontiers in Microbiology, 2023)
Nitrogen (N) as an essential macronutrient affects the soil nutrient cycle, microbial community abundance, and metabolic function. However, the specific responses of microorganisms and metabolic functions in rhizosphere soil of Phellodendron chinense Schneid seedlings to N addition remain unclear. In this study, four treatments (CK, N5, N10 and N15) were conducted, and the soil physicochemical properties, enzyme activities, microbial community abundances and diversities, metabolism, and gene expressions were investigated in rhizosphere soil of P. chinense Schneid. The results showed that N addition significantly decreased rhizosphere soil pH, among which the effect of N10 treatment was better. N10 treatment significantly increased the contents of available phosphorus (AP), available potassium (AK), ammonium nitrogen (NH4 + -N), nitrate nitrogen (NO3 --N) and sucrase (SU) activity, as well as fungal diversity and the relative expression abundances of amoA and phoD genes in rhizosphere soil, but observably decreased the total phosphorus (TP) content, urease (UR) activity and bacterial diversity, among which the pH, soil organic matter (SOM), AP, NH4 + -N and NO3 --N were the main environmental factors for affecting rhizosphere soil microbial community structure based on RDA and correlation analyses. Meanwhile, N10 treatment notably enhanced the absolute abundances of the uracil, guanine, indole, prostaglandin F2α and γ-glutamylalanine, while reduced the contents of D-phenylalanine and phenylacetylglycine in rhizosphere soil of P. chinense Schneid seedlings. Furthermore, the soil available nutrients represented a significant correlation with soil metabolites and dominant microorganisms, suggesting that N10 addition effectively regulated microbial community abundance and metabolic functions by enhancing nutrient cycle in the rhizosphere soil of P. chinense Schneid seedlings.